Positional distribution of fatty acids in natural edible oils and structured lipids / Kok Wai Ming - Kok , Wai Ming (2017)
The main objective of the present study is to investigate the positional fatty acids in natural dietary oils and structured lipids, which has shown relevance to health impact. Quantitative NMR method is selected to analyse the positional fatty acids profiles, instead of using conventional chromatographic techniques. In the present study, long chain ethyl esters were synthesised and subsequently used as starting material in the design of prospective structured lipids to reduce obesity risk. Ethyl behenate was esterified by behenic acid (C22:0) and ethanol under optimised condition. In the effort to monitor the esterification reaction, acid value and glyceride analyses were carried out. Immobilised lipase from the strain of Rhizomucor miehei (Lipozyme RM IM, NovozymesTM) was employed in the solvent-free interesterification of ethyl behenate and palm olein (IV= 56) or high-oleic sunflower oil (IV= 92). The newly synthesised structured lipids were subjected to regiospecific analysis by using quantitative 13C NMR (qCNMR) and chromatographic techniques. The structured lipids synthesised using high-oleic sunflower oil (EIE-HOS) contain higher amounts of the desired molecular species 1,3-dibehenoyl-2-oleoylglycerol (BOB) and 1-behenoyl-2,3-dioleoylglycerol (BOO) (76.5%) compared to that from palm olein (EIE-POo) (45.6%). Based on their slip melting point (SMP) (EIE-POo= 39.80°C; EIE-HOS= 41.40°C) and solid fat content (SFC), both structured lipids may find potential applications in functional dietary fats, such as cocoa butter equivalent, bakery shortening and trans-fat-free margarine. They may also serve as the hard stock for physical blending with other softer cooking oils with the aim of reducing obesogenic effects. A quick and easy analytical method using quantitative 13C NMR (qCNMR) was developed to detect and quantify erucic acid in edible oils and mustard products in this study. An unreported peak at 173.1799 ppm was detected in mustard oil and proposed as cis-13 MUFA. The regiospecific analysis method was attainable within 58 minutes without sample destruction and laborious procedures. Besides, the current method demonstrated high accuracy and low detection limit 0.98% (m/m) in quantitative results. The total content of erucic acid showed an excellent quantitative relation between conventional method (gas chromatography) and quantitative 13C NMR. In this study, selected mustard oil (21.41%) and mustard product C (8.89%) exceeded the permitted maximum levels established for erucic acid (European Union: 5%, United States: 2%). High contents of erucic acid has been reported to cause myocardial lipidosis and heart lesions. More attention should be paid to the tolerable intake of erucic acid because over consumption of erucic acid has no nutritional effect. Thus, quantitative 13C NMR (qCNMR) can be applied to monitor and quantify erucic acid content in a broad range of edible oils and mustard products.